Migraine headache in children: recent diagnosis and treatment - Winarno, Agus Nur Salim (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Migraine headache is one of the most frequent primary headaches that occur in children. It is estimated that 6 million children and adolescent in the United States suffer from migraine. Migraine can affect the quality of life and it can cause a financial and social burden. Migraine is often ignored by not only the parents and teacher but also the doctor. The diagnosis of migraine in children is challenging. Precise diagnosis and management are needed to avoid further impact. In this review, it will be discussed how to diagnose and to establish recent management of migraine in children.